2022
DOI: 10.1111/rode.12943
|View full text |Cite
|
Sign up to set email alerts
|

Rural development in the digital age: Does information and communication technology adoption contribute to credit access and income growth in rural China?

Abstract: Information and communication technology (ICT) plays an important role in rural livelihoods and household well-being. Therefore, this study examines the impact of ICT adoption on farmers' decisions to access credit and the joint effects of ICT adoption and access to credit on household income using 2016 China Labour-force Dynamics Survey data. Both recursive bivariate probit model and a selectivity-corrected ordinary least square regression model are employed for the analysis. The results show that ICT adoptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 72 publications
(114 reference statements)
1
17
0
Order By: Relevance
“…In the medium‐ and long‐run, previous studies (Briggeman & Whitacre, 2010; Galperin & Fernanda Viecens, 2017) find that promoting education and off‐farm employment in rural areas would enhance internet use of rural population. Evidence from Vietnam's neighbouring countries such as China (Ma et al, 2023) and Thailand (Nguyen, Nguyen, & Grote, 2022) also support these measures.…”
Section: The Heterogeneous and Distributional Impacts Of Internet Use...mentioning
confidence: 94%
See 1 more Smart Citation
“…In the medium‐ and long‐run, previous studies (Briggeman & Whitacre, 2010; Galperin & Fernanda Viecens, 2017) find that promoting education and off‐farm employment in rural areas would enhance internet use of rural population. Evidence from Vietnam's neighbouring countries such as China (Ma et al, 2023) and Thailand (Nguyen, Nguyen, & Grote, 2022) also support these measures.…”
Section: The Heterogeneous and Distributional Impacts Of Internet Use...mentioning
confidence: 94%
“…The internet is spreading rapidly and has become an essential part of economic and human development in both developed and developing countries (World Bank, 2021a). Internet use enables households to access a wealth of information, knowledge and educational resources, expand and strengthen social networks, improve professional skills, and increase employment opportunities (Chen et al, 2022; Ma et al, 2023; United Nations, 2018). Moreover, it could reduce transaction costs, promote innovation, create new jobs, improve labour productivity, and contribute to resource conservation (FAO, 2018; Zheng & Ma, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the pace of the fourth industrial revolution, the digital gender divide has been determined as a critical challenge to achieving gender equality (Kuroda et al, 2019). The impact of digitalization on gender equality, income, and employment has attracted considerable research interest (Alozie & Akpan-Obong, 2017;Bayes, 2001;Dettling, 2017;Hilbert, 2011;Ma, Grafton, et al, 2020;Ma et al, 2023;Rotondi et al, 2020;Viollaz & Winkler, 2022). For example, mobile phone technology in rural Uganda improves household income, gender equality, and nutrition (Sekabira & Qaim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The studies in question generally found that ICT had positive effects on the above‐mentioned elements. The main aspects of the positive effects of ICT on agriculture and rural development include: (1) technology adoption (Abate et al, 2023; Aker, 2011; Gao et al, 2020), (2) agricultural productivity and performance (Aker & Ksoll, 2016; Kaila & Tarp, 2019; Lio & Liu, 2006; Ogutu et al, 2014; Zheng & Ma, 2023), (3) income diversification (Leng et al, 2020), (4) market participation and activities (Fan & Salas Garcia, 2018; Muto & Yamano, 2009; Tadesse & Bahiigwa, 2015), and (5) credit access (Ma et al, 2023; Munyegera & Matsumoto, 2018; Sekabira & Qaim, 2017a).…”
Section: Introductionmentioning
confidence: 99%